YET MORE ON TAX ALLOCATION. - Harwood, Dale S. (The Accounting Review, 1961)
Abstract Robert Jaedicke and Carl Nelson in their article "The Allocation of Income Taxes–A Defense," published in the April 1960 issue of the journal "The Accounting Review" propose a slightly different point from which to view the argument for the inter-period allocation of the tax differential arising from the application of accelerated depreciation for tax purposes only. Subsequently Arnold Johnson in his article "More on Income-Tax-Allocation Accounting," published in the January 1961 issue of the journal summarized his position against period allocation of the tax differential, concluding that the statement of income for a given corporation for a given year should contain a deduction only for the income taxes payable to the U.S. Treasury for that year. Johnson's article, though following in time, made no overt reference to the earlier Jaedicke-Nelson article and is taken here as an independent element of the continuing debate on tax allocation. The intention of the present article is rebuttal on the Jaedicke-Nelson arguments. While along the way it hopes to provide evidence supporting Johnson's position that "allocation lacks the proof of either a legal liability or of a current asset value," the present effort centers itself in the following funds framework; the one in which Jaedicke and Nelson place their arguments.